Refractory pouchitis: does it reflect underlying Crohn's disease?. Issue 11 (November 1993) - Subramani, K; Harpaz, N; Bilotta, J; Bodian, C; Rubin, P H; Janowitz, H D; Gelernt, I M; Sachar, D B
Abstract : Typical 'pouchitis' is a well recognised complication of ileal pouches in ulcerative colitis. Infrequently, a refractory pouchitis (RP) presents with certain clinical, endoscopic, and pathological features resembling Crohn's disease and is often ascribed to misdiagnosis of the initial colitis. To test that hypothesis and to identify risk factors for RP, this study reviewed cases of presumed ulcerative colitis with ileal pouches constructed at The Mount Sinai Hospital between 1973 and 1986. Twenty four cases with RP (16 Kock pouches and eight pelvic pouches) and 21 controls were compared for eight clinical variables. The original colectomy slides from 15 RP and 18 control cases were reviewed blindly, classified into five histological categories (corresponding to definite ulcerative colitis, definite Crohn's disease, and three indeterminate groups), and scored for 23 histological features. There were no significant clinical differences between RP and control cases except for more frequent extraintestinal manifestations (38% v 5%) and male preponderance (79% v 43%) in RP. There were also no significant differences between the distributions of RP cases and controls among the five histological categories or in the 23 histological features studied. Refractory pouchitis therefore does not seem to reflect underlying Crohn's disease, but may be linked to immunological mechanisms that are manifested clinically as extraintestinal complications.